79.1k views
0 votes
Using the order of operations, what should be done first to evaluate (-4)^2 + 6 ÷ (-3 + 4)(2) - 5

User Rick M
by
5.6k points

1 Answer

3 votes

Answer:

23

Step-by-step explanation: PEDMAS

Simplify the following:

(-4)^2 + 6/(4 - 3)×2 - 5

(6×2)/(4 - 3) = (6×2)/(-3 + 4):

(-4)^2 + (6×2)/(4 - 3) - 5

-3 + 4 = 1:

(-4)^2 + (6×2)/1 - 5

(6×2)/1 = 6×2:

(-4)^2 + 6×2 - 5

(-4)^2 = 16:

16 + 6×2 - 5

6×2 = 12:

16 + 12 - 5

| 1 | 6

+ | 1 | 2

| 2 | 8:

28 - 5

| 2 | 8

- | | 5

| 2 | 3:

Answer: 23

User Splintor
by
5.7k points